Images for Instruction: A Multilingual Illustrated Dictionary in Fifteenth-Century Sultanate India - Gupta, Vivek (Muqarnas, 2021)
Abstract This article focuses on the Miftāḥ al-Fużalāʾ (Key of the Learned) of Muhammad ibn Muhammad Daʾud Shadiyabadi (ca. 1490). The Miftāḥ is an illustrated dictionary made in the central Indian sultanate of Malwa, based in Mandu. Although the Miftāḥ’s only illustrated copy (British Library Or 3299) contains quadruple the number of illustrations as Mandu’s famed Niʿmatnāmah (Book of Delights) and is a unicum within the arts of the Islamicate and South Asian book, it has received minimal scholarly attention. The definitions in this manuscript encompass nearly every facet of Indo-Islamicate art history. The Miftāḥ provides a vocabulary for subjects including textiles, metalwork, jewelry, arms and armor, architecture, and musical instruments. The information transmitted by the Miftāḥ is not limited to the Persian, Hindavi, Turki, and Arabic language of the text, but also includes the visual knowledge depicted in paintings. Through an analysis of this manuscript as a whole, this study proposes that the Miftāḥ’s manuscript was an object of instruction for younger members of society and utilizes wonder as a didactic tool.